DIFFUSE URBANISATION AND IRREGULAR URBAN GROWTH: PROCESSES AND TRENDS IN MEDIUM-SIZED CITIES IN THE CASTILLA Y LEÓN REGION (SPAIN) - López, Gonzalo Andrés; González González, María Jesús (Finisterra, 2019)
The process of extension and growth of medium-sized cities towards their surrounding municipalities in recent years has not occurred in a linear or fully defined manner. Instead, in most of these intermediate nuclei, urban growth has been diffuse and irregular, generating processes of discontinuous extension. By virtue of the types of uses implemented in recent urbanization, different spatial impacts have occurred and, moreover, each dynamic has been affected in a specific way by the economic crisis, which has slowed down and / or paralyzed many of these developments initiated in the final years of the 20th century. This paper reflects on how these urbanization processes have taken place in medium-sized cities in the region of Castile and León, proposes an analysis of recent trends which, since 2000, have configured complex and diverse urban areas around the central nuclei of these cities.